SISTEM PENDUKUNG KEPUTUSAN PENERIMA PROGRAM BANTUAN SOSIAL COVID-19 MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) (STUDI KASUS: DESA KOBA, BANGKA TENGAH) - Ningrum, Endah Sulistyo; Heryana, Nono; Voutama, Apriade (Jurnal informasi dan komputer, 2023)
The Decision Support System (DSS) for Covid-19 Social Assistance Program recipients using the Simple Additive Weighting (SAW) method helps the government in selecting the right and fair recipients of the social assistance program. The SAW method calculates the score of prospective recipients by considering criteria such as housing conditions, employment, income, dependents, and age. After the score is calculated, the system provides recommendations regarding the prospective recipients of the social assistance program that should be prioritized. The advantage of the SAW method is its ability to consider multiple criteria simultaneously and give weight to each criterion. Therefore, the Decision Support System for Covid-19 Social Assistance Program recipients using the SAW method can be used as a reference by the government in selecting the right recipients of the Covid-19 social assistance program.